“Efecto de la aplicación de materia orgánica (pollaza) en el cultivo de col china (brassica rapa lour.) variedad kiboho 90F-1, bajo las condiciones agroecológicas del distrito de Lamas” - Pusma Montenegro, David (2015)
The present qualified work of investigation "effect of the applicatíon of organic matter (pollaza) in the cultivation of Chinese cabbage (Brassica rapa Lour.) Kiboho range 90 f-1 under the ecological conditions of the District of Lamas"; had specific objectives to assess the effects of the applicatíon of three doses of organic matter (pollaza) in the cultivation of Chinese cabbage (Brassica rapa Lour.) Variety Kiboho 90 F-1 under the ecological conditions of the District of Lamas, perform economic analysis each treatment to determine the best dose. lt was established in Fundo Horticultura! "The Pacific", in the district and provínce of Lamas, statístical block design was used completely randomized (DBCA) with four blocks, four treatments and a total of 16 experimental units, treatments doses were studied Pollaza: to =; witness T1 = 1 O t.ha-1 T2 = 20; t.ha-1 T3 = 30 t.ha-1 . lncreasing doses of Organic Matter (pollaza) compared to the control treatment was adjusted to a response function increased plant height, stem diameter, diameter of the strips, T3 treatment (30 t.ha-1 MO) reached the highest average weight of 4.44 kg plant, plant height and stem diameter with 44.45 cm and 2.22 cm statistically outperforming treatments. All treatments reportad economic benefits, which shows that T2 (20 t.ha-1 ) reached the highest ratio B/C and net profit to 1.60 and S /. 14, 477.78, followed by T3 (30 t.ha-1 ), T1 (10 t.ha-1 ) and TO (witness) treatments who reached net profit of S /. 14, 070.28, S /. 11264.90 and S l. 9730.24 respectively. Key words: Performance, Pollaza, benefit I cost, weight.